2017
DOI: 10.1002/aenm.201700076
|View full text |Cite
|
Sign up to set email alerts
|

Improving Thermoelectric Performance of α‐MgAgSb by Theoretical Band Engineering Design

Abstract: α‐MgAgSb is recently discovered to be a new class of thermoelectric material near room temperature. A competitive ZT of 1.4 at 525 K is achieved in Ni‐doped α‐MgAgSb, and the measured efficiency of energy conversion reaches a record value of 8.5%, which is even higher than that of the commercially applied material bismuth telluride. On the other hand, the band structure of α‐MgAgSb is believed to be unprofitable to the power factor, owing to the less degenerate valence valleys. Here, this paper reports a syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
36
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 54 publications
(37 citation statements)
references
References 45 publications
1
36
0
Order By: Relevance
“…A record high thermoelectric conversion efficiency of 8.5% with a single thermoelectric leg operating at between 293 and 518 K has been achieved 28 . Recently, an improved ZT of 2.0 and conversion efficiency of 12.6% in Zr-and Pd-doped MgAgSb p-type materials were predicted theoretically 29 . The κ lat of these materials is 0.4 0.5 Wm −1 K −1 , comparable with that of the ultralow κ lat in SnSe originated from the strong lattice anharmonicity 22,27 .…”
mentioning
confidence: 97%
See 2 more Smart Citations
“…A record high thermoelectric conversion efficiency of 8.5% with a single thermoelectric leg operating at between 293 and 518 K has been achieved 28 . Recently, an improved ZT of 2.0 and conversion efficiency of 12.6% in Zr-and Pd-doped MgAgSb p-type materials were predicted theoretically 29 . The κ lat of these materials is 0.4 0.5 Wm −1 K −1 , comparable with that of the ultralow κ lat in SnSe originated from the strong lattice anharmonicity 22,27 .…”
mentioning
confidence: 97%
“…In contrast, numerous theoretical characterizations have focused on their local crystal structure, electronic band structure, chemical bonding, and atomic dynamics, etc. 26,27,29,33 . Additionally, to date, there have only been theoretical calculations of the phonon modes for the MgAgSb family 29,34 without any experimental verification.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In these factors, orbital energy level usually plays the major role, as it corresponds to the principal element in the Hamiltonian matrix. In previous works, the orbital energy level has been proved to be the key factor of band engineering design for cubic IV‐VI compounds [ 35 ] and α‐MgAgSb, [ 36 ] while crystal field effect and spin orbit coupling have been indicated as the key factors for Zintl‐phase Mg 3 Sb 2 . [ 37 ]…”
Section: Resultsmentioning
confidence: 99%
“…On comparing the results on S with those reported for CoRuMnAs and CoRhMnAs, we found that the maximum value of S , S max in our systems (lies in the range 26–28 μV/K) is less than that found in CoRuMnAs and CoRhMnAs 36 . However, various methods like carrier doping, nanostructuring, and chemical modification 61‐64 can enhance the TE performance of the materials. We hope that, these methods might be effective in the achievement of better TE performance in the present materials.…”
Section: Structural Propertiesmentioning
confidence: 99%